Retained Acetylated Histone Four in Bull Sperm Associated With Fertility - Ugur, Muhammet Rasit; Kutchy, Naseer Ahmad; Menezes, Erika Bezerra de; Ul-Husna, Asma; Haynes, Bethany Peyton; Uzun, Alper; Kaya, Abdullah; Topper, Einko; Moura, Arlindo; Memili, Erdogan (Frontiers in Veterinary Science, 2019)
Bull fertility, ability of the sperm to fertilize and activate the egg and support embryo development, is vital for cattle reproduction and production. Even though majority of histones are replaced by protamines, some histones are retained in sperm. It is known that chromatin remodeling during spermatogenesis results in dynamic changes in sperm chromatin structure through post-translational modifications (PTM) of sperm histones, which are important for regulation of gene expression. However, amounts of sperm Histone 4 (H4), its acetylated form (H4 acetyl), and to what extent these molecular attributes influence sperm chromatin structure and bull fertility are unknown. These gaps in the knowledge base are important because they are preventing advances in the fundamental science of bovine male gamete and improvement of bull fertility. The objective of this study was to test the hypothesis that expression dynamics as well as PTM of sperm H4 are associated with bull fertility. Flow cytometry was utilized to quantify H4 and H4 acetylated form in sperm from seven high and seven low fertility Holstein bulls. The results indicated that the average number of cells with H4 or H4 acetyl expression in high and low fertility bull sperm were 34.6 ± 20.4, 1.88 ± 1.8, 15.2 ± 20.8, and 1.4 ± 1.2, respectively. However, the sperm enriched in both H4 and H4 acetyl were different between high and low fertility groups (3.5 ± 0.6; 1.8 ± 0.8; P = 0.043). The localization and detection of H4 and H4 acetylation were measured by immunocytochemistry which revealed that H4 and H4 acetylation were equally distributed in the sperm head of high and low fertility sires. Western blotting results confirmed the presence of the H4 and its acetylated form in the sperm. Bioinformatics studies demonstrated that H4 is highly conserved among mammalians, and have significant gene ontology on spermatogenesis, early embryo implantation, and sperm capacitation. The results are significant because it demonstrates the replacement of canonical histone H4 into modified H4 acetylation in sperm and regulate its dynamics which is crucial for bull fertility and reproductive biotechnology. These findings advance fundamental science of mammalian early development and reproductive biotechnology.